The Visual Acuity of Rats in Touchscreen Setups - Els Crijns (Vision, 2019)
Touchscreen setups are increasingly used in rodents for a wide range of cognitive tasks, including visual discrimination. The greater automation and high throughput of this platform could greatly facilitate future vision research. However, little information is available regarding decision distance and on the limitations of stimulus size. Especially when studying visual functions, the lack of control of basic visual properties is a drawback. Therefore, we determined the maximal number of cycles per screen gratings can have so that Long Evans rats can reliably perform orientation discrimination. To relate our results to literature on visual acuity we tried to make an estimate of the decision distance in the touchscreen platform. The rats can discriminate between orientations with 70% accuracy up to 44 cycles per screen. This could roughly translates to the previously reported visual acuity of 1 c/degree assuming a viewing distance of 12.5 cm. This could be useful when designing new stimuli based on published results in c/degree. One could assume a viewing distance of 12.5 cm and expect similar discrimination performance in the touchscreen setup as in other tasks with a predefined viewing distance.